(untitled) (London Journal of Medical and Health Research, 2023)
Acne is one of the most common skin pathologies, one of the causes is Propionibacterium acnes, an anaerobic and gram-positive microorganism that lives in the hair follicles of the skin, currently presents resistance to antibiotic based treatments; this research topic has the purpose of evaluating the antibiotic activity of Cannabidiol oil against Propionibacterium acnes, Staphylococcus aureus and Staphylococcus epidermidis and the level of toxicity against Artemiasalina. For the methodology, antibiograms were used by the Kirby-Bauer method, where the concentrations were evaluated: 0,8 %; 0,6 %; 0,4 %; 0,3 % and 0,1 %; Amoxicillin for positive control and Dimethyl sulfoxide (DMSO) for negative control; the percentage of inhibition against Propionibacterium acnes and two control bacteria were calculated: Staphylococcus aureus and Staphylococcus epidermidis. Once the percentage of inhi-bition was tested, a toxicity study was carried out against Artemia salina to determine its LD50. The Cannabidiol oil obtained from the Ecuadorian company was used as the antibiotic agent to be evaluated, and it was found that at a concentration of 0,8% it presented a percentage of inhibition of 91,2 %; 98,7 % and 93,6 % against Propionibacterium acnes, Staphylococcus aureus and Staphylococcus epidermidis, respectively, data that do not present a significant difference against amoxicillin; for the Artemia salina test, a LD50 of 4,8 % was obtained; taking into account that the commercial oil has a presentation of 1,6 % (500 mg/30 mL), it results in a relatively innocuous product. Thus concluding that Cannabidiol oil is a very promising antibiotic due to the inhibition percentages presented and low toxicity.